Perception of the difficulties of international postgraduate students writing research proposal - Dorcas Oteng Acheampong (Center for Humanities and Innovation Studies, 2021)
International postgraduate candidates of Universities in Nanjing come from diverse backgrounds and experiences. These students face several problems, especially in writing the research proposals. The purpose of this study was to investigate the perceptions of postgraduate students in writing the research proposal. The quantitative research design was used, which involved the use of online questionnaires. A sample of 320 international postgraduate students and 20 supervisors selected at random from Universities in Nanjing were used for the study. Study findings pinpoint towards the general problems to international postgraduate students' research proposal writing skills. Grounded on the results, the researcher concludes that identifying research gaps, reviewing and criticizing literature, and finding enough evidence to support the research proposal are significant problems for most postgraduate students in writing the research proposal. The study further concludes that these problems are due to lack of research materials, time constraints, low level of engagement with supervisors, and supervisors' hostile attitude. Understanding the language and concept of research is not a reason for postgraduate difficulties in a research proposal as identified by other literature. In this regard, the solutions to these problems for postgraduate students are effective supervision, students cultivating the habit of reading sufficient literature, supervisors giving equal attention to international postgraduate students, ample time for research, timely feedback, and supervisors' availability.